ByzRev 06.2024.048: Anthony Kaldellis, The New Roman Empire: A History of Byzantium.: Oxford: Oxford University Press 2024. - Todorov, Boris (The Byzantine Review, 2024)
Anthony Kaldellis, The New Roman Empire: A History of Byzantium. Oxford: Oxford University Press 2024. xxiv + 1133 pp., 8 plates. – ISBN 978-0-197-54932-2 (hardback)